Vietnam : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Vietnam. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Vietnam's dynamic economy continues to perform well, aided by sound economic fundamentals. Growth moderated to 6.2 percent in 2016, reflecting the impact of a drought and land salinization on agriculture and lower oil production. Weakness in the oil sector continued in the first quarter of 2017, but the underlying growth momentum remains robust underpinned by strong manufacturing activity and foreign direct investment, robust domestic demand, and a rebound in agricultural production. For 2017, growth is projected at 6.3 percent and headline inflation is projected to stabilize at about 5 percent as administered prices continue to be adjusted.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet